Gas injection capacity of low permeability reservoirs considering microscopic characteristics - Yongxin MA; Qiaoliang ZHANG; Jinqi ZHU; Shuai MA; Xin WANG; Runhua ZHU (Shiyou shiyan dizhi, 2025)
Gas injection is a crucial method for enhancing oil recovery in low permeability reservoirs, but current evaluation methods for gas injection capacity have not fully considered microscopic pore characteristics. Therefore, taking the low permeability reservoirs in the fourth member of the Oligocene Weizhou Formation in well block 3 in the middle block of the Weizhou B Oilfield, Beibuwan Basin as the research object, a gas-phase effective permeability evaluation model was established based on dynamic correction of static logging permeability, comprehensively considering microscopic pore-throat structural characteristics (such as fractal dimension, throat radius, and tortuosity) and the thickness of bound water film. At the same time, core multiple-cycle gas flooding experiments were used to verify the accuracy of the evaluation model, and the seepage patterns of gas injection under the influence of microscopic characteristics were analyzed. The results showed that the gas injection capacity in low permeability reservoirs undergoes three evolutionary stages: In the initial stage of gas injection (0 to 100 PV), gas preferentially displaces crude oil in larger pores, leading to a rapid reduction in bound water saturation and a sharp increase in gas-phase permeability, which significantly improves gas flooding efficiency. In the middle stage of gas injection (100 to 1 200 PV), the gas-phase effective permeability increases linearly, and the bound water enters a stable phase due to capillary force constraints in microscopic throats. In the later stage of gas injection (>1 200 PV), gas begins to break through the water film in microscopic pores, causing a slow decrease in bound water saturation. However, due to the hydrophilicity and heterogeneity of reservoirs, residual oil are trapped as an isolated phase, leading to the stabilization of gas-phase permeability and displacement efficiency (with a maximum of 52%), and limiting the development potential of reservoirs. Field verification in the Weizhou B Oilfield demonstrated that increasing injection pressure in the initial stage can effectively improve gas injectivity index, while in the later stage, it is necessary to control the gas injection amount to prevent oil phase isolation in heterogeneous reservoirs and rising water cut in production wells, thereby ensuring oil phase precipitation and improving the overall reservoir gas flooding efficiency.